Preface to special issue on Inductive Logic Programming, ILP 2017 and 2018 - Lachiche, Nicolas; Vrain, Christel; Riguzzi, Fabrizio; Bellodi, Elena; Zese, Riccardo (Machine learning, 2019)
Inductive Logic Programming (ILP) is a field at the intersection of Machine Learning and Logic Programming, based on logic as a uniform representation language for expressing examples, background knowledge and hypotheses.